Preparation method of covalent organic framework coated titanium-silicon molecular sieve core-shell structure and in-situ photocatalytic application thereof
By coating the surface of titanium silicate molecular sieves with a covalent organic framework layer to form TS-1@COFs composite material, the problems of high energy consumption and hydrogen peroxide stability in ethylene glycol synthesis were solved, achieving efficient and green ethylene glycol preparation with a significant increase in yield.
Patent Information
- Application Number
- CN202611089498.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-22
- Publication Date
- 2026-11-06
AI Technical Summary
Existing technologies for ethylene glycol synthesis involve high energy consumption, generate a large amount of waste, and pose safety hazards. In addition, the instability of hydrogen peroxide makes storage and transportation difficult and limits the stability of the catalyst. Photocatalytic synthesis of hydrogen peroxide has failed to effectively solve the problem of in-situ generation.
By modifying titanium-silicon molecular sieve particles with a dual-ligand method and coating them with a covalent organic framework layer through thermal polymerization, a TS-1@COFs composite material was formed, which enabled photocatalytic production of hydrogen peroxide from pure water and in-situ promotion of ethylene oxidation hydration to prepare ethylene glycol.
Under solar irradiation, TS-1@COFs materials can efficiently generate hydrogen peroxide and ethylene glycol, with yields of 1017.7791 μmol/g/h and 60.043 mmol/g/h, respectively. The process is green, low-consumption, and easy to industrialize.
Smart Images

Figure CN123038876A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of materials science and technology, specifically to a method for preparing a tandem photocatalytic material and its application in the in-situ promotion of ethylene oxidation hydration to prepare ethylene glycol through photocatalytic hydrogen peroxide production. Background Technology
[0002] Ethylene glycol (EG) is an extremely important chemical, currently mainly synthesized industrially via a two-step thermocatalytic process. However, this process is extremely energy-intensive, generates large amounts of waste such as carbon dioxide, and involves the accumulation of flammable and explosive intermediates, posing serious safety hazards and environmental pollution problems. The one-pot oxidation and hydrolysis of ethylene using hydrogen peroxide (H2O2) aqueous solution to produce EG has attracted widespread attention and is considered a potential alternative to EG production due to its simplicity and environmental friendliness. However, the added H2O2 used in this route is typically synthesized via a multi-step anthraquinone process, resulting in high energy consumption and the generation of large amounts of organic waste. Furthermore, the instability of H2O2 makes its storage and transportation difficult, often requiring the addition of acids and halides for stabilization. However, these additives limit catalyst stability and corrode the reactor.
[0003] Photocatalytic synthesis of H2O2 uses renewable sunlight as input to drive the conversion of oxygen and water into H2O2 to meet the needs of on-demand production and in-situ applications. It has become a promising alternative technology for H2O2 generation, which will effectively solve the problem of adding H2O2 in the EG preparation process.
[0004] Titanium silicate molecular sieves exhibit a typical topological channel structure, with titanium sites in the framework possessing unique catalytic activation properties, enabling efficient activation of hydrogen peroxide hydration agents. Titanium silicate molecular sieves also possess advantages such as environmental friendliness, high selectivity, and low corrosivity. However, addressing the in-situ generation of hydrogen peroxide remains a challenge. Covalent organic frameworks, on the other hand, are crystalline porous frameworks formed by covalently linked organic building blocks, possessing a long-range ordered π-conjugated structure that enables directional migration of photogenerated charges. Covalent organic frameworks also offer advantages such as large specific surface area, precisely controllable structure, and excellent chemical stability. Combining covalent organic frameworks with titanium silicate molecular sieves to form a composite material can generate hydrogen peroxide in situ under light irradiation, promoting the oxidative hydration of ethylene, enabling the green and efficient preparation of ethylene glycol, overcoming the difficulties of high energy consumption, numerous steps, and high costs associated with existing processes. Summary of the Invention
[0005] The technical problem to be solved by this invention is to provide a covalent organic framework-coated titanium silicate molecular sieve core-shell structure (TS-1@COFs) for in-situ generation of hydrogen peroxide to promote the oxidative hydration of ethylene to prepare ethylene glycol. TS-1@COFs exhibits good tandem catalytic performance, demonstrating strong photocatalytic hydrogen peroxide production from pure water under solar irradiation, with a yield of up to 1017.7791 μmol / g / h, while simultaneously generating 60.043 mmol / g / h of ethylene glycol.
[0006] To address this technical problem, this invention employs a dual-ligand method to modify titanium-silicon-1 molecular sieve particles, and further coats the surface of the modified titanium-silicon-1 molecular sieve particles with a covalent organic framework layer via thermal polymerization to obtain TS-1@COFs, i.e., a photocatalyst. Ultimately, TS-1@COFs exhibits excellent catalytic performance under solar irradiation in synthesizing hydrogen peroxide from pure water and promoting the in-situ oxidation of ethylene to ethylene glycol.
[0007] The preparation method of TS-1@COFs described in this invention is as follows: Step 1: Add titanium silicon-1 molecular sieve (TS-1) to deionized water and disperse it evenly, controlling the concentration at 10-30 mg / mL; then add an equal volume of polyethyleneimine (PEI) aqueous solution with a concentration of 1-10 mg / mL dropwise, and stir for 0.5-1.5 hours; wash with deionized water by centrifugation, collect the centrifuged substrate and dry it to obtain modified TS-1 powder sample; Step 2: Add the modified TS-1 obtained in Step 1 to anhydrous acetonitrile containing 30–90 mg of polyvinylpyrrolidone (PVP), controlling the concentration to be 0.25–0.75 mg / mL; then add 2,5-diaminobenzonitrile and terephthalaldehyde in a molar ratio of (0.65–0.85):1, stir, add 400–800 μL of glacial acetic acid, react at room temperature for 3–5 hours, then add 1.2–3.6 mL of acetic acid aqueous solution, heat and stir at 80–100°C for 6–18 hours; centrifuge, wash, and dry the centrifuged substrate to obtain a covalent organic framework-coated titanium silicate molecular sieve core-shell structure (TS-1@COFs).
[0008] Preferably, in step one, the concentration of TS-1 is 20 mg / mL, the concentration of PEI aqueous solution is 5 mg / mL, and the stirring time is 1 hour, which can form a uniformly dispersed suspension.
[0009] Preferably, in step two, the polyvinylpyrrolidone is 60 mg, the modified TS-1 concentration is 0.5 mg / mL, the molar ratio of 2,5-diaminobenzonitrile to terephthalaldehyde is 0.85, the volume of glacial acetic acid is 600 μL, the reaction time at room temperature is 4 hours, the volume of acetic acid aqueous solution is 2.4 mL, the heating temperature is 80°C, and the heating time is 12 hours, which can yield TS-1@COFs with excellent crystallinity.
[0010] TS-1@COFs can be used to generate hydrogen peroxide in situ to promote the oxidative hydration of ethylene to prepare ethylene glycol.
[0011] Furthermore, this patent also discloses the application of TS-1@COFs as a tandem photocatalyst in catalyzing the production of hydrogen peroxide from pure water under solar irradiation and then in situ oxidizing ethylene hydrate to prepare ethylene glycol. The specific method steps are as follows: Step 1: Prepare a TS-1@COFs dispersion with a concentration of 0.04–0.06 mg / mL; Step 2: Irradiate using a xenon lamp source with a power of 200-400 W.
[0012] Preferably, the concentration of the TS-1@COFs dispersion is 0.05 mg / mL, and the xenon lamp light source power is 300 W, which is beneficial for the separation and purification of the product. Beneficial effects
[0013] 1. This invention employs an in-situ coating method to prepare a novel covalent organic framework-coated titanium-silicon molecular sieve composite material TS-1@COFs. This material possesses a unique porous framework structure and synergistic catalytic performance. The outer covalent organic framework can enrich the reaction substrate under light irradiation and efficiently generate 1017.7791 μmol / g / h of hydrogen peroxide in situ. The inner titanium-silicon molecular sieve can exert catalytic activation advantages. The two work synergistically to significantly improve the utilization rate of active sites and charge transfer efficiency, enabling efficient generation of hydrogen peroxide and promoting the oxidative hydration reaction of ethylene, achieving stable and efficient preparation of ethylene glycol with a yield of up to 60.043 mmol / g / h.
[0014] 2. The patented method is stable, green and low-consumption, has excellent catalytic performance, strong reusability, and is easy to prepare on an industrial scale. It has broad application prospects and extremely high practical value in the field of green synthesis of ethylene glycol in fine chemical industry. Attached Figure Description
[0015] Figure 1 The images are scanning electron microscope images of (a) TS-1, (b) TS-1@COFs and (c) TS-1@COFs described in this invention.
[0016] Figure 2(a) Potential changes, (b) Infrared spectroscopy and (c) Thermogravimetric analysis of TS-1@COFs.
[0017] Figure 3 (a) UV-Vis diffuse reflectance spectrum, (b) photocurrent response, and (c) impedance spectrum of TS-1@COFs.
[0018] Figure 4 Image showing the performance of TS-1@COFs in producing hydrogen peroxide in pure water.
[0019] Figure 5 Image showing the performance of TS-1@COFs in producing ethylene glycol under pure water and ethylene conditions. Detailed Implementation
[0020] The present patent will be further explained below with reference to specific implementation methods. Example 1
[0021] Step 1: Synthesis of modified titanium-silicon-1 molecular sieve (TS-1) particles: 100 mg of titanium silicate-1 molecular sieve (TS-1) was added to 5 mL of deionized water and dispersed evenly to a concentration of 20 mg / mL. Then, 5 mL of polyethyleneimine (PEI) aqueous solution with a concentration of 5 mg / mL was added dropwise. The mixture was stirred for 1 hour, washed with deionized water by centrifugation at 10,000 rpm for 10 minutes, and the centrifuged substrate was collected and dried at 60 °C to obtain modified TS-1 nanoparticles.
[0022] Step 2: Synthesis of TS-1@COFs: 30 mg of the modified TS-1 obtained in step one was added to anhydrous acetonitrile containing 60 mg of polyvinylpyrrolidone (PVP) to form a homogeneous dispersion with a concentration of 0.5 mg / mL. Then, 2,5-diaminobenzonitrile and terephthalaldehyde were added in a molar ratio of 0.85:1, and after stirring, 600 μL of glacial acetic acid was added, and the reaction was carried out at room temperature for 4 hours. Next, 2.4 mL of aqueous acetic acid solution was added, and the mixture was heated and stirred at 80°C for 12 hours. Finally, the substrate was washed by centrifugation with tetrahydrofuran and ethanol, respectively, dried at 60°C, and centrifuged to obtain TS-1@COFs.
[0023] Step 3: Application of the obtained TS-1@COFs in the catalytic production of hydrogen peroxide from pure water under solar irradiation 10 mg of TS-1@COFs was dispersed in 20 mL of deionized water and placed in a photocatalytic reactor. A 300 W xenon lamp was used as the light source. At 10-minute intervals (0, 10, 20, 30, 40, 50, and 60 minutes), 2 mL of the dispersion was collected and centrifuged to remove TS-1@COFs. 1 mL of the supernatant was then collected, and the hydrogen peroxide concentration was determined using the potassium iodide method: 3 mL of a potassium iodide-potassium hydrogen phthalate mixture was added, and the mixture was reacted for 4 minutes. The absorbance was measured at 350 nm using a UV-Vis absorption spectrum. The concentration of hydrogen peroxide generated by the catalytic reaction was determined using a standard curve established with commercially available hydrogen peroxide.
[0024] Step 4: Application of TS-1@COFs in in-situ oxidation of hydrated ethylene to ethylene glycol under solar irradiation 10 mg of TS-1@COFs was dispersed in 20 mL of deionized water and placed in the photocatalytic reactor. Saturated ethylene was passed through the reactor, and a 300 W xenon lamp was used as the light source. 2 mL of the dispersion was taken every 1 hour at intervals of 0, 1, 2, 3, 4, 5, and 6 hours. After centrifugation to remove TS-1@COFs, 1 mL of the supernatant was taken, and the ethylene glycol concentration was detected by gas chromatography. Example 2
[0025] The difference between this embodiment and Example 1 is that the amount of acetic acid aqueous solution added in step three is 1.2 mL, while the rest is the same as in Example 1. Example 3
[0026] The difference between this embodiment and Example 1 is that the amount of acetic acid aqueous solution added in step three is 3.6 mL, while the rest is the same as in Example 1. Example 4
[0027] The difference between this embodiment and Example 1 is that in step three, the mixture is heated and stirred at 80°C for 6 hours; otherwise, it is the same as Example 1. Example 5
[0028] The difference between this embodiment and Embodiment 1 is that in step three, the mixture is heated and stirred at 80°C for 18 hours; otherwise, it is the same as Embodiment 1.
[0029] Through Example 1, Figure 1 These are scanning electron microscope and transmission electron microscope images of different samples obtained in this invention. Figure 1 (a) indicates that the TS-1 particles are nanometer-sized, about 300 nm, with a relatively smooth and uniform surface. Figure 1 (b) shows that after the modified TS-1 was coated with COFs, the particle size increased significantly to about 400 nm, and the surface became rough. Figure 1(c) is a transmission electron microscope image of TS-1@COFs. It can be seen that a core-shell structure was formed after COFs were coated in situ on the surface of modified TS-1, with TS-1 as the core and COFs as the shell. Through Example 1, Figure 2 The results show the physicochemical structural characterization of different samples prepared in this invention. Figure 2 The potential test results in (a) show that the TS-1 surface is negatively charged. After the introduction of PEI and PVP, the potential changes to positive charge, indicating that the assembly strategy is successful. After the in-situ polymerization growth of the COFs layer, the surface becomes negatively charged again, which is beneficial to the subsequent adsorption of reaction substrates. Figure 2 (b) The infrared spectrum of TS-1@COFs showed multiple characteristic peaks belonging to COFs, indicating that the polymerization and coating of COFs was successful. Figure 2 (c) indicates that since COFs are organic components, they are not resistant to high temperatures, thus the thermal stability of TS-1@COFs will decrease. Thermogravimetric analysis shows that TS-1 itself has high thermal stability, but the thermal stability decreases after COFs are coated on its surface, further demonstrating the successful synthesis of the COFs layer on modified TS-1.
[0030] Through Example 1, Figure 3 The electronic structure characterization results of different samples prepared in this invention are shown. Figure 3 (a) shows that after introducing a COFs layer on the modified TS-1 surface, the light absorption capacity of TS-1@COFs is significantly improved and the light response range is expanded. Figure 3 (b) shows that TS-1@COFs have the ability to generate more photogenerated carriers and significantly improve carrier separation efficiency. Figure 3 (c) indicates that TS-1@COFs have a faster charge transfer capability.
[0031] Through Example 1, Figure 4 This invention describes the photocatalytic hydrogen peroxide production performance of TS-1 and TS-1@COFs. For example... Figure 4 As shown in (a), using air and pure water as raw materials, TS-1@COFs can generate 508.9 μM hydrogen peroxide within 60 minutes, while TS-1 has almost no hydrogen peroxide generation performance. Figure 4 (b) shows that the yield of TS-1@COFs is as high as 1017.7791 μmol / g / h, indicating that it has excellent photocatalytic performance.
[0032] Through Example 1, Figure 5This study examines the tandem photocatalytic performance of TS-1 and TS-1@COFs for the production of ethylene glycol. The results show that TS-1 exhibits no ethylene glycol production without the addition of hydrogen peroxide, while TS-1@COFs demonstrates excellent tandem catalytic performance by promoting the oxidative hydration of ethylene to ethylene glycol through photocatalytic hydrogen peroxide generation, achieving a yield of 60.043 mmol / g / h.
Claims
1. A method for preparing a titanium silicalite molecular sieve core-shell structure TS-1@COFs coated with a covalent organic framework, characterized in that, Includes the following steps: Step 1: Add titanium silicon-1 molecular sieve TS-1 powder to deionized water, controlling the concentration at 10-30 mg / mL; then add an equal volume of polyethyleneimine (PEI) aqueous solution with a concentration of 1-10 mg / mL, stir for 0.5-1.5 hours; then wash with deionized water by centrifugation, collect the centrifuged substrate, dry it, and obtain modified TS-1. Step 2: Add the modified TS-1 obtained in Step 1 to anhydrous acetonitrile containing 30–90 mg of polyvinylpyrrolidone (PVP), controlling the concentration at 0.25–0.75 mg / mL; then add 2,5-diaminobenzonitrile and terephthalaldehyde in a molar ratio of (0.65–0.85):1, stir, add 400–800 μL of glacial acetic acid, and react for 3–5 hours; then add 1.2–3.6 mL of acetic acid aqueous solution, heat and stir at 80–100°C for 6–18 hours; centrifuge, wash, and dry the centrifuged substrate to obtain the covalent organic framework-coated titanium silicate molecular sieve core-shell structure TS-1@COFs.
2. The production method according to claim 1, characterized by, In step one, the concentration of TS-1 is 20 mg / mL, the concentration of PEI aqueous solution is 5 mg / mL, and the stirring time is 1 hour.
3. The preparation method according to claim 1, characterized in that, In step two, the PVP concentration is 60 mg; the modified TS-1 concentration is 0.5 mg / mL; the molar ratio of 2,5-diaminobenzonitrile to terephthalaldehyde is 0.85; the volume of glacial acetic acid is 600 μL, and the reaction time is 4 hours; the volume of the acetic acid aqueous solution is 2.4 mL, the heating temperature is 80°C, and the heating time is 12 hours.
4. The covalent organic framework-coated titanium-silicon molecular sieve core-shell structure TS-1@COFs obtained by the preparation method according to claim 1.
5. The TS-1@COFs obtained by the preparation method according to claim 4, characterized in that: The TS-1@COFs are used as a tandem photocatalyst to catalyze the production of hydrogen peroxide from pure water under solar irradiation and to oxidize ethylene hydrate in situ to prepare ethylene glycol.
6. The TS-1@COFs according to claim 5, characterized in that: The application involves preparing a TS-1@COFs dispersion at a concentration of 0.04–0.06 mg / mL and irradiating it with a xenon lamp source with a power of 200–400 W.
7. The TS-1@COFs according to claim 5 or 6, characterized in that, In this application, the concentration of TS-1@COFs is 0.05 mg / mL, and the xenon lamp light source power is 300 W.
